Landform and Landscape in Africa - Pritchard, J.M (Edward Arnold Publishers Ltd, 1979)
The aim of this book is to create a greater awareness and understanding among students living in Africa of the processes which are moulding the landforms and landscapes of their own continent$1! =s
Keywords: Landform Africa; Non-Fiction